Deep coma in a child treated with propranolol for infantile hemangioma - Ilirjana Bakalli; Elmira Kola; Robert Lluka; Ermela Celaj; Durim Sala; Inva Gjeta; Sashenka Sallabanda; Dea Klironomi (BMC, 2019)
Abstract Background Propranolol hydrochloride is the first-line agent recommended for the treatment of infantile hemangiomas (IH). Serious adverse effects of propranolol therapy for hemangiomas are infrequent. Case presentation We report a case presented in deep hypoglycemic coma during his treatment with propranolol for IH. Through our case report and the review of the literature, we aimed to underline the importance of recognizing adverse effects during propranolol therapy. Although propranolol has a long history of safe and effective use in infants and children, pediatricians should be aware that life-threatening adverse effects can happen during propranolol therapy for IH. Conclusion Early identification of these adverse effects can be of great importance for patient management and prognosis. It must certainly be noted that not just early identification among doctors, but education for parents is crucial.